Andrew Carnegie's mental dynamite : unlock the awesome power of you - Hill, Napoleon, 1883-1970 (Sterling, 2020)
"When Andrew Carnegie laid out his principles of success to young Napoleon Hill, he inspired Hill to expand on that philosophy, leading to the bestselling Think and Grow Rich and a series of motivational pamphlets. Now, the Napoleon Hill Foundation has selected three principles from those booklets for elaboration: Self-Discipline, Learning from Defeat, and the Golden Rule"--